Optimised coordinate generation for Arduino-based focus and motion control system for deployment in time-lapse photography - Johannes Jacobus Myburgh; Nicolaas Johannes Luwes (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This paper demonstrated the design and implementation of a unique algorithm used to generate interim coordinates for focus transitions in time-lapse photography. Through a prototype design methodology, the unique algorithm was developed to function within the limitations imposed by a low-cost 8-bit microcontroller for the development of a cost-effective focus and motion control system for deployment in photographic higher education. Through conceptualization and virtualization in MathLab and comparison with values generated in simulated real-world use-case, the proposed algorithm was tested for function and efficacy in generating interim coordinates that included focus coordinate estimation to facilitate smooth non-linear motion with focus transitions during image sequence capture. The 8-bit Arduino Mega 2560 proved capable of completing calculations required by the developed algorithm and generated coordinate data sets identical to sets generated in simulation. The generated coordinated illustrated effective user-defined control over motion and the smoothness of focus transitions. The developed algorithm is thus capable of facilitating the required movement and focus transition coordinate calculation and estimation required while deployed on a low-cost 8-bit microcontroller and is well suited for deployments in time-lapse capture applications.